Clinical Practice Guidelines for Subarachnoid Haemorrhage Treatment - José Ramón Tejera del Valle; Danny Barrueta Reyes; Joaquín Aguilar Trujillo; José Gómez Cruz; Líder Tejera Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Subarachnoid Haemorrhage Treatment. The concept, diagnosis, classification and treatment are reviewed in its different stages, including aspects of the neurosurgical treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.